Broadband high responsivity large-area plasmonic-enhanced multilayer MoS2 on p-type silicon photodetector using Au nanostructures. (4th September 2019) - Tan, Chee Leong; Wei, Heming; Thandavam, Tamil Many K; Ramli, Rizal; Park, Minsu; Ahmad, Harith
Abstract: High responsivity, large-area plasmonic-enhanced nanostructure photodetector based on multilayer (ML) molybdenum disulfide (MoS2 ) deposited on p-type Silicon (Si) substrates is reported. A large area ML-MoS2 is deposited onto the Si photodetector (PD) using a modified membrane filtration method. This large area ML-MoS2 and Au NSs on the p-Si form a cavity-like structure that dramatically enhances the incident light path. The increase of incident light path due to light trapping effect enhances the electron-hole pair generation tremendously. The plasmonic-enhanced ML MoS2 on Si PD has achieved a stable and repeatable photoresponse up to 37 A W −1, whereas the detectivity is around 10 12 Jones at the broad wavelengths (405–780 nm) with a modulation frequency of 1 kHz. The enhancement of photoresponsivity is 8, 5.3 and 11 times with 5 V bias at an incident wavelength of 405 nm, 650 nm and 780 nm respectively as compared to the bare p-Si PD. The experimental results also show that the plasmonic-enhanced ML-MoS2 on Si PD exhibited fast photoresponse (rise time of ∼1 μ s and fall time of ∼18 μ s), which is much higher compared to typical transition metal dichalcogenide PD or single layer MoS2 based PD. These excellent performances show that the plasmonic-enhanced MoS2 structure is highly potential to apply in Si photovoltaics, visible range photodetection, and visible bio/chemical sensing application.